Peningkatan Nutrisi Pupuk Organik Cair Dari Limbah Pemurnian Minyak Nilam Menggunakan EM4 - Titien Sara; Syaifullah Muhammad; Sri Aprilia (Fakultas Teknik, 2021)
The production of patchouli oil refining the largest waste in Indonesia. But still has high nutrient content and can be used as liquid organic fertilizer. To increase the efficiency of the formation of liquid fertilizer from patchouli waste requires the role of EM4 bioactivator and chicken manure. The study aims to determine the production of liquid organic fertilizer froom potchouli waste with EM4 bioactivator and the addition of chicken manure as well as to analyze the effect of fermentation time and EM4 solution to obtain maximum N, P, K content. The results showed that there were some effect of fermentation time and variable of EM4 on NPK content. The maximum solution of N in the variable 8% EM4 solution with fermrntation time of 3 days was 0.34%. The maximum P in the variable of 4% EM4 solution with a fermentation time of 9 days was 0.10%. The maximum K in the variable of 2 and 4% EM4 solution with a fermentation time of 5 days were 0.27%.